Clinical characteristics, causes, adherence to heart failure treatment guidelines and mortality of patients with acute heart failure: the Groote Schuur Hospital experience - Szymanski, Patryk Zygmunt (Department of Medicine, 2017)
Background: There is limited information on acute heart failure (AHF) and the treatment thereof in sub-Saharan Africa. Therefore, the aim of this study was to describe the clinical characteristics, causes, adherence to heart failure (HF) treatment guidelines and mortality of patients presenting to Groote Schuur Hospital with acute heart failure (AHF). Methods: This is a sub-study of The Sub-Saharan Africa Survey of Heart Failure (THESUSHF). This sub-study is a prospective and observational survey that focused on the enrolment and follow-up of additional patients with AHF presenting to Groote Schuur Hospital entered into the existing registry, following the publication of the primary paper of THESUS-HF in 2012. The patients were classified into prevalent (or existing) or incident (or new) cases of heart failure. Results: Of the 119 patients included, 69 (58%) were female and the mean (SD) age was 49.9 (16.3) years. Prevalent cases were mostly of mixed ancestry (63.3%) with more hypertension (70%), diabetes mellitus (36.7%), hyperlipidaemia (33.3%) and ischaemic heart disease (36.7%) than incident cases. The main causes of heart failure were cardiomyopathy (20.2%), ischaemic heart disease (IHD) (19.3%) and rheumatic valvular heart disease (RHD) (18.5%). Most patients received renin-angiotensin system blockers and loop diuretics on discharge. There was a low rate of β-blocker, aldosterone antagonist and digoxin use. Rehospitalisation at 180 days occurred in 25.2%. In-hospital mortality was 8.4 % and the case fatality rate at six months was 26.1%. Conclusion: In Cape Town the main causes of AHF are cardiomyopathy, IHD and RHD. AHF affects a young population and is associated with a high rate of rehospitalisation and mortality. There is a serious under-use of β-blockers, aldosterone antagonists and digoxin. An emphasis on the rigorous application of treatment guidelines is needed in order to reduce re-admission and mortality.